Modeling the age-specific per capita growth and reproduction of Rhizobius lophanthae (Col: Coccinellidae) - Cividanes, F. J.; Gutierrez, A. P. (Lavoisier Abonnements, 1996)
A per capita model for the growth, development and reproduction of the coccinellid predator Rhizobius lophanthae (Blaisd) feeding on the oleander scale (Aspidiotus nerii Bouche (Homoptera: Diaspididae)) was developed. A thermal threshold for development of 9.4 degrees C was found. Under conditions of unlimited food, the relationship of mass at time t+1 to that at t (in days at 25 degrees C) suggests an 8.7 percent growth rate per mg larvae per day at 25 degrees C. An adult female beetle produces approximately 20 eggs per day while consuming an average of 8.5 scales/day. This is approximately 2.16 eggs per scale consumed above the maintenance level of 1.88 scales per day. More precisely, this compensation point is 0.12 mg of prey/mg of predator/day at 25 degrees C and the egestion rate is 1 - beta = 0.63.
Keywords: Rhizobius lophanthae; energy flow; metabolic pool model; oleander scale